Influence of Different Factors on Permanent Deformation of Hot Asphalt Concrete Mixtures - Albayati, Amjad H.; Al-Mosawe, Hasan (Civil and environmental engineering (Berlin), 2023)
The performance of flexible pavements is significantly impacted by the permanent deformation (rutting) of asphalt pavements. The research aims was to evaluate the permanent deformation of asphalt mixtures under different conditions. To achieve this aim, 108 cylindrical specimens have been prepared and tested under repeated loading in uniaxial compression mode. Five factors were considered in this research. They include testing temperature, loading conditions (stress level and duration), and mixture properties (bitumen type and content). The permanent deformation is evaluated in term of the following parameters, permanent micro strain , resilient micro strain , initial permanent strain (intercept, ), accumulation rate of permanent deformation (slope, ), rate of decrease in permanent deformation and constant of proportionality between permanent and elastic strains . The test results showed that the and are increased as the testing temperature increased. In addition, the value for load duration of 0.4 s is 1.64 times the value for 0.1 s. Finally, the findings showed that the resilient response of the material is comparatively more sensitive to bitumen content than the plastic response. Furthermore, the rutting resistance is highly affected by the variables considered in this research.